2023
DOI: 10.1007/s15010-023-02021-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of antiparasitic therapy for neurocysticercosis in rural Tanzania: a prospective cohort study

Abstract: Purpose Neurocysticercosis is common in regions endemic for Taenia solium. Active-stage neurocysticercosis can be treated with antiparasitic medication, but so far no study on efficacy and safety has been conducted in Africa. Methods We conducted a prospective cohort study on treatment of neurocysticercosis in Tanzania between August 2018 and January 2022. Patients were initially treated with albendazole (15 mg/kg/d) for 10 days and followed up for 6 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Treatment may include medications to address the infection, manage symptoms, and control inflammation. Antiparasitic medications, such as albendazole or praziquantel, are often used to treat the disease [113]. In some cases, corticosteroids may be prescribed to reduce inflammation.…”
Section: Neurocysticercosismentioning
confidence: 99%
“…Treatment may include medications to address the infection, manage symptoms, and control inflammation. Antiparasitic medications, such as albendazole or praziquantel, are often used to treat the disease [113]. In some cases, corticosteroids may be prescribed to reduce inflammation.…”
Section: Neurocysticercosismentioning
confidence: 99%
“…Indeed, lesions compatible with NCC were found in approximately 9% of participants in various neuroepidemiological studies conducted in rural communities of Mexico (States of Puebla and Morelos) [5,6]. Despite its usually benign evolution, clinical studies have shown that cysticidal treatment improves the evolution of P-NCC [7][8][9]. The other form of NCC, known as extraparenchymal neurocysticercosis (EXP-NCC), occurs when the parasite is located outside the parenchyma, frequently in the ventricles or in the subarachnoid space at the basal cisterns [10].…”
Section: Introductionmentioning
confidence: 99%